Correlação entre a taxa de fertilização e o fuso meiótico em oócitos humanos: Uma meta-análise - Petersen, Claudia Guilhermino; Oliveira, João Batista Alcantara [UNESP]; Mauri, Ana Lucia; Massaro, Fabiana C.; Baruffi, Ricardo; Pontes, Anaglória [UNESP]; Franco Junior, Jose Gonçalves [UNESP] (My University, 2009)
Objective: To investigate the relationship between the presence of meiotic spindle in human oocytes and fertilization rates in ICSI cycles. Methods: Search strategies included online surveys of databases from 1990 to 2008. Nine trials fulfilled the inclusion criteria Results: According to the meta-analysis, the results showed statistically significant higher fertilization rate (p<0.0001) when the meiotic spindle was viewed than when it was not. There was heterogeneity in this comparison. Conclusion: The presence of a birefringent meiotic spindle in human oocytes can predict a higher fertilization rate. This observation has clinical relevance mainly in countries where there is a legal limit on the number of oocytes to be fertilized. Copyright - SBRA - Sociedade Brasileira de Reprodução Assistida.
Correlation between fertilization rates and meiotic spindle in human oocytes: A meta-analysis
Keywords: Fertilization rate; Human oocyte; ICSI; Meiotic spindle; Meta-analysis; clinical trial; data analysis; data base; fertilization; human; information retrieval; intracytoplasmic sperm injection; meiosis; meiosis spindle; meta analysis; oocyte; oocyte maturation; systematic review